CUSTOMER SATISFACTION ON SERVICE QUALITY IN PRIVATE COMMERCIAL BANKING SECTOR IN BANGLADESH - Al Karim, Rashed; Chowdhury, Tabassum (British Journal of Marketing Studies, 2014)
Customer satisfaction is essential for the success of service firms like bank. The quality of service has become an aspect of customer satisfaction. Day by day it has been proven that service quality is related to customer satisfaction. This study endeavors to discover the impact of service quality on customer satisfaction in private sector banks in Bangladesh. Five dimensions in service quality (servqual) such as tangibility, reliability, responsiveness, empathy, and assurance (Parasuraman, Zeithaml, & Berry, 1985) are considered as the base for this study. A structured questionnaire with 5 point Likert scale has been used to collect the data by conducting survey. The sample size is 110 and is chosen on a convenient basis. Data has been analysed by using SPSS software (version: 17). Result of the study showed that tangibility, reliability, responsiveness, assurance and empathy significantly and positively influenced customer attitudes in terms of satisfaction that is service quality dimensions are crucial for customer satisfaction in private commercial banking sector in Bangladesh.